German Librarianship and Munich Libraries - Osman Ümit Özen (Türk Kütüphaneciliği)
There are 27 municipal libraries including the Central Public Library in Munich. The other important libraries in the city are Bayern State National Library, Maximillian University Library, a technical highschool library and the "Deutsches Musuem" Library. All these libraries are financed locally. The author introduces these libraries briefly and compares German libraries with Turkish libraries. He concludes that although theoretically there are not distinctive differences, in practice, buildings and their layout are better in Germany where more variety of services are offered. In Turkey standardization has not been realized yet. Turkey needs to computerize and network to improve the services offered in an efficient way.